ANALISIS PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) TERHADAP PENCAPAIAN TARGET SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Soni, Soni; Juita, Erna; Risdawati, Renny (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
The problem of limited electrical energy in various rural areas. The dominant use of fossil fuels also has a negative impact on the environment, including in Ranah Pesisir District, Pesisir Selatan Regency. Micro Hydro Power Plants (MHP) are seen as an environmentally friendly renewable energy solution with the potential to improve community welfare. This study aims to analyze the contribution of Micro Hydro Power Plants (MHP) to achieving the SDGs goals and analyze local community responses to their existence. The method used is a qualitative approach with a case study. Qualitative data obtained through interviews, surveys, and literature reviews are then analyzed descriptively to assess the relationship between MHP development and SDGs goal indicators. The results show that MHP has a positive impact on increasing access to electrical energy, creating jobs, and encouraging community economic activities. MHP also contributes to equitable energy access, increasing productivity, and reducing dependence on fossil fuels. However, MHP development poses ecological challenges, such as changes in river flow and potential disruption to local ecosystems.